Influence des changements agraires sur la dynamique paysagère autour des aires protégées du complexe Pô-Nazinga-Sissili au Burkina Faso - Adama Zoungrana; Marjolein Visser; Charles De Cannière; Pingdewindé Carine Ouédraogo; Babou André Bationo; Salifou Traoré (Tropicultura, 2023)
Understanding the drivers of landscape fragmentation is essential to reduce the anthropisation impact on ecosystems and enhance biodiversity conservation. However, the principles of landscape ecology alone are not sufficient to understand the influence of agrarian change on landscape dynamics. This study adopts an integrated approach based on the principles landscape ecology and sociology to analyze the impact of land tenure on landscape dynamics in the vicinity of protected areas. A multichronic analysis using Landsat satellite imagery and individual surveys with farmers were carried out. Five land cover classes, seven landscape metrics and three agro-demographic indices were used to interpret changes in the landscape in relation to agrarian dynamics. A new spatial index was introduced to quantify the process of shortening of fallow land. By comparing two villages with contrasting land tenure systems and similar demographic growth, the results show that the renting of agricultural land contributes to landscape fragmentation and is responsible for the loss of 37.97% of fallow land. This dynamic creates permanent land tenure insecurity and is a constraint on the adoption of sustainable agricultural practices. Considering the land tenure disparity within the farmers would reduce landscape fragmentation.